Sizing up the crowd: Assessing spatial integration difficulties in body size judgements across eating disorder symptomatology - Turnbull, Georgia; Lego, Sophia; Kennedy, Briana L.; Alexi, Joanna; Li, Yanqi R.; Engel, Manja M.; Mann, Georgina; Bayliss, Donna M.; Farrell, Simon; Bell, Jason (Frontiers in Psychology, 2023)
Body size judgements are frequently biased, or inaccurate, and these errors are further exaggerated for individuals with eating disorders. Within the eating disorder literature, it has been suggested that exaggerated errors in body size judgements are due to difficulties with integration. Across two experiments, we developed a novel integration task, named the Ebbinghaus Illusion for Bodies, to assess whether nearby bodies influence the perceived size of a single body. Virtual reality (VR) was used to simulate the appearance of a small crowd around a central target body. Our first experiment (N = 412) revealed an Ebbinghaus Illusion, in which a central female appeared larger when surrounded by small distractors, but comparatively smaller when surrounded by large distractors. In other words, the findings of Experiment 1 demonstrate that surrounding crowd information is integrated when judging an individual’s body size; a novel measure of spatial integration (i.e., an Ebbinghaus Illusion for Bodies). In our second experiment (N = 96), female participants were selected based on high (n = 43) and low (n = 53) eating disorder symptomatology. We examined whether the magnitude of this illusion would differ amongst those with elevated versus low eating disorder symptomatology, in accordance with weak central coherence theory, with the high symptomatology group displaying less spatial integration relative to the low group. The results of Experiment 2 similarly found an Ebbinghaus Illusion for Bodies. However, illusion magnitude did not vary across high and low symptomatology groups. Overall, these findings demonstrate that surrounding crowd information is integrated when judging individual body size; however, those with elevated eating disorder symptomatology did not show any integration deficit on this broader measure of spatial integration.